Bilateral fibrodysplasia ossificans affecting the masticatory muscles and causing irreversible trismus in a domestic shorthair cat. Issue 1 (April 2019) - Guzu, Michel; Gaillot, Hugues A; Rosati, Marco; Nicolier, Alexandra; Hennet, Philippe R
Case summary: An 8-year-old spayed female domestic shorthair cat was referred for trismus of progressive onset, which had started at least 1 month previously. The patient presented with weakness, anorexia, chronic bilateral purulent nasal discharge and concurrent reduced nasal airflow. Upon physical examination, painful mouth opening, bilateral swelling of the temporal areas, with an inability to open and close the mouth completely, were apparent. A vertical mandibular range of motion (vmROM) of 22 mm was noted. Complete blood count, biochemistry, electrolytes and various serology tests were unremarkable. CT revealed multiple mineralised lesions within the masticatory muscles. Histopathological features were consistent with those seen in the human disease fibrodysplasia ossificans progressiva (FOP). Supportive treatment did not improve the vmROM, eventually resulting in a 13 mm open bite, and total inability to close and open the mouth. Cardiac arrest occurred at the induction of an anaesthesia procedure aiming to perform tracheostomy and nasal lavage. Despite emergency tracheotomy and cardiac resuscitation, humane euthanasia was elected by the owners. Post-mortem molecular investigations highlighted a heterozygous deletion, compatible with a splicing site mutation in ACVR1, which is also associated with FOP in humans. Relevance and novel information: This is the first report in the veterinary literature of FOP-like disease selectively affecting the masticatory muscles. This condition is associated with a poor prognosis, as no medical or surgical treatment has currently proven to be of any prophylactic or curative benefit. Although rare, FOP-like disease should be included in the differential diagnosis of trismus in the cat. Any further muscle injury should be avoided.